Precision Medicine for Alzheimer’s Disease Prevention - Berkowitz, Cara L. (Healthcare (Basel), 2018)
Precision medicine is an approach to medical treatment and prevention that takes into account individual variability in genes, environment, and lifestyle and allows for personalization that is based on factors that may affect the response to treatment. Several genetic and epigenetic risk factors have been shown to increase susceptibility to late-onset Alzheimer’s disease (AD). As such, it may be beneficial to integrate genetic risk factors into the AD prevention approach, which in the past has primarily been focused on universal risk-reduction strategies for the general population rather than individualized interventions in a targeted fashion. This review discusses examples of a “one-size-fits-all” versus clinical precision medicine AD prevention strategy, in which the precision medicine approach considers two genes that can be commercially sequenced for polymorphisms associated with AD, apolipoprotein E (APOE), and methylenetetrahydrofolate reductase (MTHFR). Comparing these two distinct approaches provides support for a clinical precision medicine prevention strategy, which may ultimately lead to more favorable patient outcomes as the interventions are targeted to address individualized risks.